Pengembangan Aplikasi Media Pembelajaran Wordwall bagi Siswa Kelas V pada Mata Pelajaran PAI SDN Banjardowo 1 Jombang - Astari, Susi; Ashoumi, Hilyah (MASALIQ, 2025)
A This study aims to describe the feasibility of wordwall learning media applications for grade V students in Islamic religious education subjects and to describe student responses to wordwall learning media applications for grade V students at SDN Banjardowo 1 Jombang. Product development that will be applied at SD Negeri Banjardowo 1 Jombang is in the form of wordwall learning media based on the problems that exist in the school. In this research, the development model uses ADDIE, which consists of analysis, design, development, implementation, and evaluation. This development research aims to test the feasibility of learning media, evaluate better learning outcomes, and determine student reactions to the developed application-based learning media. Based on the feasibility of wordwall application learning media from the results of the validator getting an average score of 82% and the results of material expert validation with an average score of 83% included in the very good category. At the student response stage based on the trial to 33 students, the average score was obtained to be 87 with a very good category. The results of student responses can be seen from 5 indicators in the closed questionnaire, namely: (1) students' opinions on learning based on contextual problems score percentage 81% positive category; (2) the ease of students in understanding the subject matter through a contextual approach score percentage 90% very positive category; (3) student motivation in learning that leads to concept discovery score percentage 92% very positive category; (4) student interest in learning based on real experience score percentage 91% very positive category; (5) enthusiasm for student learning with a contextual approachscore percentage 80% positive category. So it can be concluded that the wordwall application learning media is feasible to use and apply as a teaching media.